PENGARUH E-SERVICE QUALITY TERHADAP KEPERCAYAAN DAN KEPUASAN PENGGUNA GEN Z PADA E-WALLET SHOPEEPAY DI SUMATERA BARAT - Hasan; Rahmiati (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: This study aims to examine the effect of E-Service Quality on E-Trust and E-Satisfaction among Generation Z ShopeePay users in West Sumatra, as well as to investigate the mediating role of E-Trust in the relationship between E-Service Quality and E-Satisfaction. This research employed a quantitative approach using a survey method. Data were collected through an online questionnaire distributed to 400 respondents selected using purposive sampling. The data were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach with SmartPLS 4 software. The results revealed that E-Service Quality has a positive and significant effect on E-Trust (β = 0.582; p < 0.001) and E-Satisfaction (β = 0.359; p < 0.001). Furthermore, E-Trust was found to have a positive and significant effect on E-Satisfaction (β = 0.363; p < 0.001). The mediation analysis indicated that E-Trust partially mediates the relationship between E-Service Quality and E-Satisfaction, with an indirect effect value of 0.211 (p < 0.001). These findings suggest that improving electronic service quality can enhance user satisfaction both directly and indirectly through increased user trust in ShopeePay. This study contributes to the digital marketing and consumer behavior literature and provides practical insights for digital wallet service providers in improving service quality, strengthening user trust, and increasing customer satisfaction. Keywords: E-Service Quality, E-Trust, E-Satisfaction, ShopeePay, Gen Z.   Abstrak: Penelitian ini bertujuan untuk menganalisis pengaruh E-Service Quality terhadap E-Trust dan E-Satisfaction pengguna e-wallet ShopeePay dari kalangan Generasi Z di Sumatera Barat serta menguji peran mediasi E-Trust dalam hubungan tersebut. Penelitian menggunakan pendekatan kuantitatif dengan metode survei melalui penyebaran kuesioner secara daring kepada 400 responden yang dipilih menggunakan teknik purposive sampling. Data dianalisis menggunakan metode Partial Least Squares Structural Equation Modeling (PLS-SEM) dengan bantuan perangkat lunak SmartPLS 4. Hasil penelitian menunjukkan bahwa E-Service Quality berpengaruh positif dan signifikan terhadap E-Trust (β = 0,582; p < 0,001) dan E-Satisfaction (β = 0,359; p < 0,001). Selain itu, E-Trust juga berpengaruh positif dan signifikan terhadap E-Satisfaction (β = 0,363; p < 0,001). Hasil pengujian mediasi menunjukkan bahwa E-Trust mampu memediasi secara parsial pengaruh E-Service Quality terhadap E-Satisfaction dengan nilai pengaruh tidak langsung sebesar 0,211 (p < 0,001). Temuan ini mengindikasikan bahwa peningkatan kualitas layanan elektronik mampu meningkatkan kepuasan pengguna secara langsung maupun melalui peningkatan kepercayaan pengguna terhadap ShopeePay. Penelitian ini memberikan kontribusi empiris dalam pengembangan literatur pemasaran digital dan dapat menjadi bahan pertimbangan bagi penyedia layanan dompet digital dalam meningkatkan kualitas layanan, membangun kepercayaan, serta meningkatkan kepuasan pengguna. Kata kunci: E-Service Quality; E-Trust; E-Satisfaction; ShopeePay; Gen Z; Sumatera Barat